Rancang Bangun Sistem Informasi Akademik Pada SMK Informatika Ciputat Menggunakan Metode Extreme Programming - Fahmi Ramadhan; Yono Cahyono (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
In an effort to increase the use of technology and information in terms of managing student and teacher academic activities, information, inputting grades and student data, class schedules, payment of school fees, data management and student activity documents in a school has an important role. Ciputat Informatics Vocational School. Until now, there is no system that can process student data, value data, ease of transacting school fees. Everything is still using the company's standard methods, both from recording on paper to ordinary excel data, and also students having to queue when they want to pay school fees, of course this is very irrelevant to the current situation. In designing an academic information system using the Extreme Programming method, the Extreme Programming model was chosen because the process is very fast and flexible in making the application. The stages themselves include planning, design, coding which includes refactoring and ends with testing. The design of an academic information system at the Ciputat Informatics Vocational School is website-based and designed with the PHP programming language, and assisted by the MYSQL database.